Enhancement of the Baltics’ secondary exchange traded equity markets through the medium of regulatory sandboxes - Miglinieks, Māris (Riga Graduate School of Law, 2020)
Financial markets are an integral part of the modern economy. The necessity for their efficiency can be undoubtedly observable empirically with the latest example being the use of financial markets in order to mitigate current pandemic economic backlash with different monetary policy mechanisms such as quantitative easing. In this thesis, the author identifies Baltics secondary exchange traded equity market environment-related problems and applies hypothetical regulatory sandbox models in order to provide partial solutions to the identified issues. In order to conduct such research, the author creates a theoretical framework for regulatory sandboxes with their commonly associated legal issue typologies and establishes financial market environment theoretical condition framework which is later assessed with empirical studies of Baltics secondary exchange traded markets and then applied in order to solve identified financial market problems by proposing hypothetical regulatory sandbox frameworks and approximate applicant guidelines Cumulatively, the thesis creates a comprehensive legal and economic market environment framework and provides experimental regulatory solutions by regulating designated market making and multilateral trading facilities.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Financial law; Financial markets